Inspection routing problem for coal mine safety personnel in underground mines. (April 2019) - Zhen, Lu; Wang, Bochen; Li, Miao; Wang, Wencheng; Huang, Lin
Highlights: This study investigates a routing problem for security personnel in coal mines. A mixed integer linear programming model is formulated. Three methods are developed for the problem. Experiments are conducted to assess the efficiency of the methods. Abstract: Coal mine safety is the foundation of coal mine enterprise development, and inspections performed by safety personnel are an indispensable part of ensuring the production of coal mines. The complex network of tunnels in underground mines restricts the efficiency of safety inspection routes; therefore, planning these routes is critical. This study investigates a routing problem in which safety personnel start from multiple sites to inspect a set of sites. A mixed integer linear programming (MILP) model is formulated to optimize the inspection routes. Three methods are used to address the problem: a local branching (LB)-based solution method, a tabu search-based solution method and a back propagation (BP) neural network method. Numerical experiments are conducted to assess the efficiency of the methods on different scales.